Pengembangan Subject Specific Pedagogy (SSP) Berbasis Problem Based Learning (PBL) untuk Menguatkan Literasi Lingkungan Siswa SMA - Syamsiyah, Nurul; Karyanto, Puguh; Prayitno, Baskoro Adi; Sapartini, Raden Rara (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
The research aims to know about the characteristic, advisability, and effectiveness of Subject Specific Pedagogy(SSP) equipment based on Problem Based Learning (PBL) to reinforce the environmental literacy of HighSchool students. Environmental literacy consists of knowledge, attitude and concern. The research used theResearch and Development method. Design of this research was using 3-D model from 4-D. This designconsists of define, design and develop, without disseminate concept. The research subject retrieval techniqueby using purposive sampling. The subjects of this research are students of SMAN 1 Surakarta has receivedenvironment’s topic in the classroom. Data collection was done through observation, documentation, questionform and interview. The data analysis techniques in qualitative and quantitative for the device include SSP,analysis question form of environmental literacy, analysis of the results from interview, the homogeneity test,normality test and Non-Paired Sample T-Test. The result of this research are: 1) the characteristic of SSPequipment based on PBL was developed by PBL steps (meeting the problem; problem analyzing; discoveryand reporting; solution, presentation, and reflection; overview, integration and evaluation) and an extradimension of the indicators based on the dimension of anti-anthropocentrism which complement the 5dimensions of the New Ecological Paradigm (NEP) in the indicators, 2) advisability of SSP was measured bytest of validity, limited test, and research subject test 3) The result of Non-Paired Sample T-Test havesignificance on the knowledge, attitude and concern are 0.000 < 0.05. H0 is rejected which showed a differencein effectiveness. The results of this research can reinforce the environmental literacy of High School students.